Diffuse Axonal Injury After Traumatic Brain Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Forty children and adolescents with traumatic brain injury and suspected diffuse axonal injury were studied for hemorrhagic lesions, using a high-resolution magnetic resonance imaging susceptibility-weighted technique, at Loma Linda University Medical Center, CA.